What is the correct first step to solve the equation −3x−13=14

for x?(1 point)
Responses

Add 3 to both sides of the equation.
Add 3 to both sides of the equation.

Add 13 to both sides of the equation.
Add 13 to both sides of the equation.

Divide both sides of the equation by -3.
Divide both sides of the equation by -3.

Subtract 13 from both sides of the equation.

1 answer

To solve the equation \(-3x - 13 = 14\) for \(x\), the first step should be to isolate the term with \(x\). Therefore, you should start by eliminating the constant term \(-13\) on the left side of the equation.

The correct first step is:

Add 13 to both sides of the equation.

This will result in:

\(-3x - 13 + 13 = 14 + 13\)

Which simplifies to:

\(-3x = 27\)

So, the correct option is "Add 13 to both sides of the equation."

Similar Questions
  1. JamalStep 1: Set equation =0 . x2+4x−12=0 Step 2: Write quadratic equation as the product of two factors. (x+6)(x−2)=0 Step
    1. answers icon 2 answers
  2. Steps to Solve a Multi-Step Equation Quick Check3 of 53 of 5 Items Question Jonny is solving this equation for n : 8 + 3n = 20 .
    1. answers icon 2 answers
  3. Below are the steps to solve an equation:Step 1: |x − 2| + 3 = 7 Step 2: |x − 2| = 7 − 3 Step 3: |x − 2| = 4 Which of
    1. answers icon 3 answers
    1. answers icon 1 answer
more similar questions